Bangsawan Bugis yang Merantau ke Kecamatan Basala - Iit Hikmayanti; La Ode Topo Jers (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
The purpose of this study was to find out the reasons why Bugis nobles migrated to Basala District and how Bugis nobles showed their identity in overseas areas. The results of this study indicate that the arrival of Bugis aristocrats in Basala District was due to a family invitation factor and the desire to improve the economy, due to the area of ​​agricultural land available and the price of land which was relatively cheap compared to their native area or in South Sulawesi. The way Bugis aristocrats show their identity with the call of Pung and the difference in dowry given to noble descendants, not only that, nobility can also be distinguished by looking at the roof of the three-story house. There are several suggestions from this research, namely, the people in the District, including the Bugis nobles, to maintain good relations, and for the government to continue to develop the culture of the people in Basala District, including the Bugis tribes who are there.